Biochemical Targets of Plant Bioactive Compounds A Pharmacological Reference Guide to Sites of Action and Biological Effects - Polya, Gideon Maxwell (Taylor & Francis, 2003)
This volume is a comprehensive and user-friendly reference guide to biochemical targets of plant defensive compounds. It presents a goldmine of succinctly summarized information relating to bioactive compound structures, plant sources, biochemical targets and physiological effects that can be readily accessed via the plant genus index and chemical compound index. With introductory chapters providing reviews of the structural diversity of plant defensive compounds and biochemistry, Biochemical Targets of Plant Bioactive Compounds is an invaluable reference for biomedical professionals in the fields of complementary medicine, natural product chemistry, toxicology, and pharmacology.